ANTIMICROBIAL RESISTANCE IN SALMONELLA ENTERICA SEROVAR TYPHI: UNDERSTANDING THE MECHANISMS AND PATHOGENICITY OF INFECTION” A COMPREHENSIVE REVIEW - ANWAR , A; AYAZ , N; AHMAD , S; HAFSA, .; NAZ , F; NADIR , K (Biological and Clinical Sciences Research Journal, 2024)
Typhoid Fever is a contagious disease caused by Salmonella enterica serovar typhi. It is also the cause of bloodstream infections in most of the developing countries. The pathogen can escape from the host’s immune response, a feature linked with the capsular structure of bacteria, which contributes to its virulence and is a crucial factor in the dissemination of infection. Salmonella enterica serovars are classified as typhoidal and nontyphoidal salmonella. In this review, we will discuss the ecumenical occurrence of immune strains of Salmonella enterica. We cover the mechanism of antimicrobial resistance in Salmonella, including plasmid-mediated resistance. Antibiotic resistance can occur through various mechanisms, such as deactivation of antibacterial medications, changes in therapeutic targets, and acquisition of foreign DNA coding for resistance determinants through horizontal gene transfer. Additionally, bacteria can employ different efflux pumps to resist antibiotics. These are some of the common ways in which antibiotic resistance is developed. We will explore the factors contributing to its virulence, such as the improper use of antibiotics, gene transfers, recurrent infections, and reduced host immunity. Proper hygiene practices and accurate treatment are necessary to combat typhoid disease, which can be better understood by studying its pathogenesis and diagnosis. The widal test and Typhidot test are essential for the diagnosis of salmonella. Vaccines are available against typhoid. We can overcome disease development through vaccination by choosing safe delivery methods and control strategies.